Strategi Guru IPS Dalam Menanamkan Nilai-Nilai Sosial Pada Siswa Kelas VII Di SMPN 1 Purwoasri Kediri - Mufidaturrohmah Priyani; Bagus Setiawan (Student Research Journal, 2023)
This research is motivated by facts in the field showing that social studies teachers are still more oriented towards assignments and students' understanding of learning material without considering the formation of student character as a learning effect, so that learning material is less affected by students' attitudes and personalities in shaping interactions between teachers and students. This makes students tend to be busy or not pay attention when the teacher is explaining, during the learning process in the classroom. Therefore, these constraints certainly need a solution so that the teaching and learning process can be channeled properly, an IPS teacher really needs to use a learning strategy that is appropriate to the material to be conveyed and is also in accordance with the IPS teacher's strategy in instilling social values. The formulation of the problems in this study are: 1) What is the social studies teacher's strategy to instill social values in social studies learning for class VII students at SMPN 1 Purwoasri? 2) What are the supporting and inhibiting factors for social studies teachers in carrying out strategies for instilling social values in class VII students at SMPN 1 Purwoasri? 3) What are the results of the IPS teacher's strategy in instilling social values in class VII at SMPN 1 Purwoasri? The objectives of this study are: 1) To find out the social studies teacher's strategy to instill social values in social studies learning for class VII students at SMPN 1 Purwoasri. 2) To identify the supporting and inhibiting factors of social studies teachers in carrying out strategies for instilling social values in class VII students at SMPN 1 Purwoasri. 3) To find out the results of the social studies teacher's strategy in instilling social values in class VII at SMPN 1 Purwoasri. The research method used is a qualitative method and this research is descriptive in nature. This research is sourced from primary data and secondary data. Data collection techniques in the form of observation, interviews and documentation. Then the data analysis technique in this study refers to the Miles and Huberman model. Checking the validity of the data, namely observation persistence, triangulation, and peer checking. The results of this study indicate that: 1) The social studies teacher's strategy in instilling social values possessed by students is through several ways, namely exemplary and continuous reprimand and habituation patterns. To instill social values in students, the teacher instills an attitude of honesty, discipline, tolerance, mutual cooperation, courtesy, confidence and responsibility (an attitude of daring to accept consequences, being able to carry out individual tasks properly, not blaming others, and always keeping promises). to students. 2) Factors that support the social studies teacher's strategy in instilling social values in students are a comfortable learning environment, there are rules in the class that are obeyed, and there is a dominant role of the teacher. On the other hand, the inhibiting factors of the social studies teacher's strategy in instilling social values in students are the teacher being late, the lack of monitoring of regulations, and the influence of friends. 3) The results of the social studies teacher's strategy in instilling social values in class VII students at SMPN 1 Purwoasri include social awareness, multicultural understanding, and social involvement which are in good condition.